2020
DOI: 10.3390/pr8020208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wall Ventilation on the Shock-wave/Viscous-Layer Interactions in a Mach 2.2 Intake

Abstract: In order to achieve proficient combustion with the present technologies, the flow through an aircraft intake operating at supersonic and hypersonic Mach numbers must be decelerated to a low-subsonic level before entering the combustion chamber. High-speed intakes are generally designed to act as a flow compressor even in the absence of mechanical compressors. The reduction in flow velocity is essentially achieved by generating a series of oblique as well as normal shock waves in the external ramp region and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As a result, the separation bubble size is decreased. Recently, the influence of a porous cavity on SBLIs, mounted inside a Mach 2.2 supersonic intake, has been studied for various intake contraction ratios by Gunasekaran et al [128]. The study revealed that the performance of a porous surface with a cavity is strongly dependent on the contraction ratio of a supersonic inlet.…”
Section: Passive Control Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the separation bubble size is decreased. Recently, the influence of a porous cavity on SBLIs, mounted inside a Mach 2.2 supersonic intake, has been studied for various intake contraction ratios by Gunasekaran et al [128]. The study revealed that the performance of a porous surface with a cavity is strongly dependent on the contraction ratio of a supersonic inlet.…”
Section: Passive Control Techniquesmentioning
confidence: 99%
“…They concluded that the MVGs induced mixed size vortices help to minimize the upstream interaction region, which in turn suppresses SBLIs. In the recent studies carried out by Kaushik [105] and Gunasekaran et al [128], the efficacy of the MVGs as well as the porous surface, deployed over a shallow cavity mounted in a Mach 2.2 mixed compression intake, have been investigated experimentally. Since the effects of passive controls in a hypersonic intake may not be the same as in the supersonic intake, therefore, an investigation into the hypersonic intake controlled with passive techniques is essential to identify their effectiveness.…”
Section: Plasma Jets (Active Control) [98-102]mentioning
confidence: 99%
“…So far, a few SWBLI flow control methods have been developed and can generally be divided into passive and active groups. The former group usually includes placing bumps, [4][5][6][7] micro vortex generators, 8,9 and cavities [10][11][12][13][14][15] at some specific positions to adjust the local energy distribution in the flow field without importing any external energy. In the latter group, the boundary layer suction [16][17][18][19][20] and blowing 21,22 techniques are most common, which require extra energy expenditure to some degree.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the off-design performances, several strategies can be adopted [10]. Some passive control approaches can be adopted in order to limit the effects of the flight Mach number, like for example the use of cavities with porous surfaces [11][12][13][14]. Alternatively, several active control systems are available.…”
Section: Introductionmentioning
confidence: 99%